Some factors for explaining resilience among young men in colombia (2000)
Based on an existing database, we explored childhood experiences that differentiated men who became delinquent or involved in substance abuse from those who did not (referred to as resilient) despite growing up in equally adverse circumstances, among a sub sample of men (n=168) included in a previous study on delinquency in five different cities in Colombia. The findings show that resilient men tend to perceive their caregiver as affectionate, available when needed, aware of their whereabouts and able to solve problems on their own more often than men who became delinquent or involved in substance abuse. They were also exposed to less physical abuse and family conflict. These findings appear to be independent of economic status (based on head of the household's occupation level), mother's level of education, mother's age at time of birth, percentage identifying the mother as primary caregiver, percentage born into single parent households, number of siblings, birth order, parental antecedents of crime or alcohol abuse or separations from parents. Although political and social reforms are necessary to guarantee appropriate living conditions equally for all, until these occur, other prevention strategies based on these findings are suggested such as empowering parents, improving the quality of parent-child interactions and mentors.